One-pot synthesis of oxazolidine-2-thione and thiozolidine-2-thione from sugar azido-alcohols - Mishra K.B.; Agrahari A.K.; Tiwari V.K. (My University, 2025)
A controlled and facile synthesis of various glycosyl 1,3-oxazolidine-2-thiones and 1,3- thiozolidine-2-thiones has been accomplished from corresponding sugar azido alcohols utilizing Staudinger reaction (PPh3 and CS2) via isothiocynate route. A series of reactions were performed to investigate the effects of CS2 and PPh3 on the selectivity of product formed. The excessive addition of CS2 with PPh3(1.2 equiv) afforded oxazolidine-2-thione alone, while the solitary addition of PPh3 for 30 min followed by addition of CS2 to the reaction mixture resulted both the products in different ratios, which were successfully isolated using column chromatography (SiO2). Furthermore, synthesis of 1,3-oxathiolan-2-imine from glycosyl epoxide has also been attempted. Structures of all the developed compounds have been elucidated using extensive spectroscopic techniques including IR, NMR and MS analysis. © 2017 Elsevier Ltd